How to baby : a no-advice-given guide to motherhood - Finck, Liana (The Dial Press, 2024)
"How do you know if you're ready to have a baby? How do you know if you might be pregnant? And how do you deal with peeing all the time and being hungry all the time and fielding well-meaning but kind of insulting advice and finding a doula and being dropped by your old friends and learning why it's called mom brain and not dad brain and spending half your life on hold with your insurance company and the tyranny of the milestones you're not meeting and negotiating boundaries with in-laws and realizing that your heart now exists outside of your chest and in the body of this tiny little being whose entire existence depends on the quality of your care? To tackle these questions and many others, award winning cartoonist and memoirist Liana Finck began illustrating her early years years of motherhood, sharing her joys, fears, and insecurities with her many fans"--